(3GdeMceI GdLfGFjI GdOhdjI (B: s (3OQGSI ehVhYjI ELQGFjI (B/ s - (3CMeO KGHJ YHO GdQMjes; (3MSfjf YHjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQIs, 2012)
(3GdeMceI GdLfGFjI GdOhdjI(B-(3OQGSI ehVhYjI ELQGFjI h gi acQI GdeMceI GdLfGFjI GdOhdjI jJfGhd GdJWhQ GdJGQjNj ddeMceI h JYQjagG h GdCSGS GdbGfhfj dgG(B: (3GdCMcGe GdehVhYjI ddeMceI GdLfGFjI GdOhdjI jJfGhd fWGb SQjGf GdfXGe GdCSGSj ddeMceI ef MjK GdLQGFe h GdCTNGU h GdReGf h GdecGf(B: (3GdCMcGe GdELQGFjI ddeMceI GdLfGFjI GdOhdjI jJfGhd GdJTcjd GdbVGFj ddeMceI h JMQjc GdOYhj GdLfGFjI h Mbhb GdCTNGU CeGe GdeMceI(B: (3GdYdGbI Hjf GdeMceI GdLfGFjI h GdbVGA GdhWfi jJfGhd GdJYGhf Hjf GdeMceI h GdOhd h GdefXeGJ h GdGNJUGU GdJcejdj ddeMceI h GdCMcGe h JfajPgG(B: (3h NdUJ GdOQGSI Edi YO fJGFL h JhUjGJ CgegG Cf gPg GdeMceI LGAJ HfGA Ydi GJaGbjI OhdjI h ecedI ddbVGA GdhWfi h JNJU HCNWQ GdLQGFe GdOhdjIs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2012.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdeMceI GdLfGFjI GdOhdjIs; (3LQGFe GdMQHs; (3GdLQGFe VO GdGfSGfjIs; (3GdeMceI GdLfGFjI GdOhdjIs; (3gjFI GdGee GdeJMOIs; (3GdbGfhf GdOhdj GdLfGFjs; (3LQjeI GdGHGOI GdLeGYjIs; (3GdLQGFe VO GdGfSGfjIs; (3GdeSFhdjI GdLfGFjI s; (3GdMUGfGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs